The Function of Mass Media in the Democracy State Perspective related to the Election Organization - Gunawan, Riyan; Ahmadi, Ahmadi (Law Research Review Quarterly, 2018)
In the implementation of democracy in Indonesia, the mass media is required to be more independent and neutral in providing information, especially regarding the conduct of elections. The mass media must be able to become social control in the socio-political life in society. In addition, the media must also be able to provide actual, factual, and balanced information to the public so that it can become a reference for the community in choosing leaders and can create elections that are in accordance with the principles of elections in democratic countries. The use of media plays an important role in the campaign process and modern political socialization. However, the mass media itself has shown a position of dilemma in supporting the implementation of democracy, even today the mass media is trying to position itself as a political actor. The position of the media caught in a conflict to maintain the ethics of journalistic interests or political interests is considered a problem. Because if the news delivered is not balanced, it could potentially harm democracy in Indonesia itself. In this case, actually the community did not get enlightenment about political issues, but rather provoked because of the imbalance of news received. This situation can be a threat in the upcoming 2019 general election, especially for the presidential election which is only followed by 2 candidate pairs. In this paper we will explain the function of mass media in a democratic perspective related to the holding elections in Indonesia.